A case report of osteoarticular mucormycosis in post COVID - 19 Patient - Shah, Bhavini; Shah, Sandip C; Toshniwal, Harsh; Dharsandiya, Mitkumar; Shah, Krutarth; Panchal, Chinjal; Agarwal, Saifali (Indian Journal of Case Reports, 2022)
Mucormycosis is a rare invasive fungal disease often seen in immuno-compromised individuals.The Mucormycosis cases increased in COVID-19 patients from March – June 2021. Here we report a case of 61 year old male hypertensive patient with COVID-19 who was treated with antibioticsand steroids for recovery. After treatment he developed secondary infection of osteoarticular mucormycosis which is uncommon and rare. We report this case here  in detail.